Sustaining success through strategies for post-elimination management of neglected tropical diseases in African Union Member States - Chotun, Nafiisah; Eaton, Julian; Anagbogu, Ifeoma Ajegbo; Tesfahunei, Hanna Amanuel; Shawa, Sheila; Karutu, Carol; Bolarinwa, Akeem; Mohammed, Abdulaziz (Frontiers in Tropical Diseases, 2024)
The elimination of Neglected Tropical Diseases (NTDs) has seen significant progress, with 22 African Union Member States having successfully eliminated at least one NTD. However, post-elimination management of NTDs remains a challenge. This article provides important insights into the challenges faced by African Union Member States after eliminating NTDs, including potential financial support withdrawal and risk of disease reemergence. We also discuss comprehensive strategies for post-elimination management, emphasising the importance of robust surveillance systems, capacity building, community engagement, and the integration of mental health services. We also advocate for a multisectoral approach to sustain elimination gains, aligning with global and regional health strategies. Our analysis underscores the necessity of continuous innovation in surveillance, the critical role of community health workers, the integration of NTD post-elimination management into broader health and development frameworks such as Universal Healthcare Coverage, and the need for innovative financing and partnerships to ensure the long-term success of NTD elimination efforts.